Seed yield and quality of African marigold (Tagetes erecta) under year-round transplanting conditions in northern plains of India - KUMAR, RAKESH; SINGH, RANJIT; KAUR, NAVJYOT; Vij, Lavanya (The Indian Journal of Agricultural Sciences, 2026)
African marigold (Tagetes erecta L.) cv. Punjab Gainda No. 1 is the most popular cultivar with bright orange marketable double flower. Being the farmers’ cultivar of choice for year-round cultivation, the problem of seed setting in summers and lack of availability of quality seed for plantations directly leads to huge economic losses. This study was carried out during 2021–2023 at Punjab Agricultural University, Ludhiana, Punjab to check the seed yield and quality of Punjab Gainda No. 1 under year-round transplanting conditions in the northern plains of India. The experiment was laid out in a randomised complete block design (RCBD) with 12 transplant dates on the 15th of each month year-round for assessing the optimum planting window for maximising seed yield and quality. Mid- July to Mid-September transplanted crops exhibited better seed yield and quality due to favourable environmental conditions supporting vegetative growth and seed filling. Mid-August transplanting yielded the highest seed yield and quality including germination rate and seedling vigour indices. Seeds from this period exhibited higher accumulation of seed reserves and higher activities of enzymes – dehydrogenase and α-amylase which play crucial roles in seed viability and germination, respectively. Conversely, winter and summer transplanting yielded poorer seed quality due to adverse climatic conditions affecting seed development. Overall, mid-August transplanting is the best time period to ensure maximum seed yield and quality in African marigold for achieving successful seed production in the northern plains of India.